Ar de Rock - Andrade, Ricardo (Contemporânea, 2023)
Songs like Chico Fininho, by Rui Veloso and the Banda Sonora, and Cavalos de Corrida, by the group UHF, were the first hits of the "Portuguese rock boom", an expression referring to the first moment of great commercial success for rock repertoire recorded and published in Portugal. At the beginning of the 1980s, "Portuguese rock" was central to the consolidation of a "modern" and cosmopolitan youth identity that increasingly identified with habits and lifestyles from the Anglo-American cultural universe. The intensification of the editorial commitment to this repertoire led to the emergence of new groups, record producers, sound companies and artist agencies, as well as the reconfiguration of the characteristics of various bands that sought to align themselves with the phenomenon, including the growing use of the Portuguese language, an aspect that until then had often been disregarded in the context of rock music. This book analyses the main changes that took place in rock practices in Portugal during the second half of the 1970s and early 1980s, looking at the links between the various music industries and the role of their agents as active participants in shaping the activity of the groups and their respective repertoires. Canções como Chico Fininho, de Rui Veloso e a Banda Sonora, e Cavalos de Corrida, do grupo UHF, constituíram os primeiros êxitos do «boom do rock português», expressão referente ao primeiro momento de grande sucesso comercial de repertório rock gravado e publicado em Portugal. No início da década de 1980, o «rock português» foi fulcral na consolidação de uma identidade juvenil «moderna» e cosmopolita crescentemente identificada com hábitos e estilos de vida provindos do universo cultural anglo-americano. A intensificação da aposta editorial neste repertório motivou o aparecimento de novos grupos, produtores fonográficos, empresas de som e de agenciamento de artistas, assim como a reconfiguração das características de várias bandas que procuraram alinhar-se com o fenómeno, inclusive no crescente recurso à língua portuguesa, aspecto até então frequentemente desprezado no âmbito do rock. Neste livro, são analisadas as principais transformações ocorridas nas práticas do rock em Portugal durante a segunda metade da década de 1970 e inícios da década de 1980, contemplando a articulação entre as várias indústrias ligadas à música e o papel dos seus agentes enquanto participantes activos na configuração da actividade dos grupos e dos seus respectivos repertórios.